A phosphoinositide 5‐phosphatase from Solanum tuberosum is activated by PAMP‐treatment and may antagonize phosphatidylinositol 4, 5‐bisphosphate at Phytophthora infestans infection sites. Issue 1 (4th October 2020) - Rausche, Juliane; Stenzel, Irene; Stauder, Ron; Fratini, Marta; Trujillo, Marco; Heilmann, Ingo; Rosahl, Sabine
Summary: Potato ( Solanum tuberosum ) plants susceptible to late blight disease caused by the oomycete Phytophthora infestans display enhanced resistance upon infiltration with the pathogen‐associated molecular pattern (PAMP), Pep‐13. Here, we characterize a potato gene similar to Arabidopsis 5‐phosphatases which was identified in transcript arrays performed to identify Pep‐13 regulated genes, and termed StIPP. Recombinant StIPP protein specifically dephosphorylated the D5‐position of phosphatidylinositol 4, 5‐bisphosphate (PtdIns(4, 5)P2 ) in vitro . Other phosphoinositides or soluble inositolpolyphosphates were not converted. When transiently expressed in tobacco ( Nicotiana tabacum ) pollen tubes, a StIPP‐YFP fusion localized to the subapical plasma membrane and antagonized PtdIns(4, 5)P2 ‐dependent effects on cell morphology, indicating in vivo functionality. Phytophthora infestans ‐infection of N. benthamiana leaf epidermis cells resulted in relocalization of StIPP‐GFP from the plasma membrane to the extra‐haustorial membrane (EHM). Colocalizion with the effector protein RFP‐AvrBlb2 at infection sites is consistent with a role of StIPP in the plant–oomycete interaction. Correlation analysis of fluorescence distributions of StIPP‐GFP and biosensors for PtdIns(4, 5)P2 or phosphatidylinositol 4‐phosphate (PtdIns4P) indicate StIPP activity predominantly at the EHM. In Arabidopsis protoplasts, expression of StIPP resulted in the stabilization of the PAMP receptor, FLAGELLIN‐SENSITIVE 2, indicating that StIPP may act as a PAMP‐induced and localized antagonist of PtdIns(4, 5)P2 ‐dependent processes during plant immunity.